The effects of intake on steers administered anabolic implants - Lee, Tiffany (Kansas State University, 2012)
The objectives of this study were to examine the effect of anabolic implants on nutrient balance, metabolic status, and growth factors in animals consuming nutrients either adequate or inadequate to support growth. Sixteen crossbred steers (BW 293 ± 19.3 kg) were trained to individual Calan gates, and randomly assigned to one of four treatments in a 2x2 factorial arrangement: (1) administration of an anabolic growth implant, and fed a moderate energy starting cattle diet at 2.0 × maintenance; (2) implant administration, and fed the same starting diet at 1.0 × maintenance; (3) no implant, and 2.0 × maintenance; (4) no implant and 1.0 × maintenance diet. Cattle were implanted with RevalorXS, containing 200 mg TBA and 40 mg estradiol. Animals were weighed on d 0, 14, and 28, with total gain, ADG, and feed efficiency determined at each time point. Blood samples were taken from each animal at d 0, 14, and 28 and used in determining serum concentrations of IGF-1 and plasma urea nitrogen (PUN). Serum collected on d 14, and 28 was applied to satellite cells (previously isolated from non-study steers and frozen). Protein abundance of myosin heavy chain (MYH; d 0, 14, and 28), phosphorylated extracellular signal related kinase (pERK; d 0 and 28), and phosphorylated mammalian target of rapamycin (pmTOR; d 0 and 28) was analyzed in differentiated satellite cells to determine effects of implant, intake, and their interaction (applied via the serum). There was a significant effect of diet on weight (P < 0.0001). There was a tendancy for an interaction between diet and implant on PUN (P = 0.09). Only diet had an effect on IGF-1 levels (P < 0.001). Implant increased MYH abundance (P < 0.01), and the abundance of pERK (P < 0.01). At high intake, implant increased abundance of pmTOR (P = 0.02) but had no effect on pmTOR at restricted intake (P = 0.21; interaction P < 0.01). These preliminary results show that implantation, which has previously been shown to improve gain, ADG, and feed efficiency, may not be as beneficial in cattle fed a restricted diet.
Keywords: Cattle; Implants; Growth; Physiology; Nutrition (0570)